A comparative perspective of local electoral management bodies in Latin America. (15th November 2021) - Romero Ballivián, Salvador
Abstract: There are not many studies on subnational electoral bodies in Latin America, especially with a comparative approach. This article describes these bodies based on their main traits and presents the first hypotheses to explain their development or atrophy. It posits that the nations' geographic extension and the complexity of the different levels of government—federalism or significant levels of mid‐level autonomy—are associated with a greater degree of institutionalization, autonomy, and strength at the subnational electoral level, such that a smaller nation, or the absence of a mid‐level government, limits consolidation. The article uses a comparative approach. Resumen: Los organismos electorales subnacionales de América Latina forman un objeto de estudio poco conocido, más aún en una dimensión comparativa. La investigación describe estas entidades a partir de sus principales rasgos y formula las primeras hipótesis explicativas sobre su desarrollo o atrofia. Plantea como eje de trabajo que la extensión geográfica de los países y la complejidad de los niveles de gobierno —el federalismo o significativos niveles de autonomía a nivel intermedio—se asocian con un mayor grado de institucionalización, autonomía y solidez del nivel electoral subnacional, en tanto que la talla reducida del país o la ausencia del nivel medio de gobierno limita su consolidación. El abordaje del trabajo es constantemente comparativo. 摘要: 关于拉美地方选举机构的研究并不多，尤其是比较研究。本文基于这些机构的主要特征对其加以描述，并提出假设以解释机构的发展或衰退。假设认为，国家的地理延伸和各级政府（联邦层面或强大的中等自治区层面）的复杂性与地方选举层面更大程度的制度化、自治权以及能力相关，这让更小的民族或中等层面政府的缺乏对民主巩固过程产生限制。本文使用了比较研究法。